CONCENTRATION OF HEAVY METALS IN GREEN MUSSELS (Perna viridis) OF LAMPUNG BAY AND THEIR SYMBIONE BACTERIAL RESISTANCE (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Green mussels are marine organisms that are threatened due to heavy metal pollution such as lead and copper in marine waters. In addition, to threatening shell organisms heavy metals are also a threat to symbiont organisms. Bacteria exposed to heavy metals continuously will later be able to adapt (resistance) to heavy metal contamination. This study aims to determine the concentration of heavy metals lead (Pb) and copper (Cu) in green mussels from Lampung Bay and to test the resistance of symbiotic bacteria to Pb and Cu as well as to conduct molecular identification to determine the type of selected symbiotic bacteria. This research was conducted by analyzing the content of heavy metals in water samples and green mussels then isolated the symbiotic bacteria and selected using Luria Bertani agar by adding heavy metal concentrations, then tested the level of resistance to Pb and Cu which were added continuously from concentrations of 100 ppm to 1000 ppm to bacteria can no longer grow optimally. After that, molecular identification was carried out to determine the type of bacteria and reconstructed to see the molecular proximity. The results showed that the water and green mussels had exceeded the quality standard and were classified as polluted. Bacterial isolates were resistant to Pb in the range of 100-1000 ppm and Cu in the range of 100-700 ppm. Molecular identification of the selected samples, namely STL09 and STL11, showed that the symbiont bacteria were a type of bacterial species Bacillus sp.